Attitude and behavior on daily food purchasing decisions in the time of COVID-19: A case study of Indonesia consumers - Widayat Widayat; Zainal Arifin (Jurnal Inovasi Ekonomi, 2020)
This investigation was carried out to exam the influence of attitudes towards COVID-19 with food on purchasing decisions of early adult consumers with a quantitative survey approach. The data relates to the attitude which includes that the virus is dangerous, difficult to cure and originates from China and purchasing decision behavior to fulfill daily food needs consists of being careful in choosing, paying attention to producers, care to the countries of origin, cashless payment usage, and paper money avoidance was collected with a four-scale style questionnaire distributed via Google form. Data obtained by the sample (n = 157) were selected using convenience methods and then analyzed by playing the Structural Equation Modeling, assisted by Smart-PLS. The result shows that attitude correlates with behavior in fulfilling daily foods. The attitudes towards the COVID-19 come from China that is dangerous, difficult to treat, contributes to cautious behavior, healthy behavior in meeting daily food needs, and purchasing payment usage. The consumer tends to the more careful in choosing, paying attention to care for the food producers, and where food comes from. Attitudes also have an impact on the preference of consumers to use E-money and paper money avoidance as an effort to avoid physical contact with the seller or supplier.